Simultaneous Improvement and Genetic Dissection of Drought Tolerance Using Selected Breeding Populations of Rice - Cui, Yanru; Zhang, Wenying; Lin, Xiuyun; Xu, Shizhong; Xu, Jianlong; Li, Zhikang (Frontiers in Plant Science, 2018)
Drought is the most important factor limiting rice yield in most rainfed areas of Asia and Africa. Four large BC2F2 populations consisted of 3,200 individuals, which were derived from crosses between an elite Geng variety, Jigeng88 and four donors from three different countries, were screened and progeny tested under severe drought stress, resulting in the development of 72 introgression lines (ILs) with significantly improved yield compared to the recurrent parent Jigeng88. These DT ILs plus four random populations (without drought selection population) from the same crosses were evaluated in replicated trials under both drought stress and non-stress conditions in two environments, and characterized with simple sequence repeat (SSR) markers to understand how directional selection was operating on the genetic variation of DT of rice. Thirteen DT QTLs of large effect were identified based on the significant allelic and genotypic frequency shits in the DT ILs by using the joint segregation distortion method. The 13 QTLs were validated by the genotypic differences at individual QTL in the random populations. Putative genetic networks consisting of 30 loci in 29 functional genetic units underlying DT were detected by X2 tests and non-random associations between or among DT loci in DT ILs from the four populations. Most large-effect DT QTLs were previously reported and located in the upstream of the genetic networks as putative regulators, and were either mapped to important regulatory genes for DT or drought responsiveness reported previously. In our study, five promising ILs with significantly improved yield were selected under both drought and normal irrigated conditions. The QTLs and their genetic networks underlying DT detected provided useful genetic information for further improving DT and yield using designed QTL pyramiding.